Analisis Profil Skripsi Mahasiswa Jurusan Tadris Biologi IAIN Kerinci - Dinyah Rizki Yanti Zebua (Symbiotic: Journal of Biological Education and Science, 2021)
This research maps the thesis profile of students, which consists of research topics, types of research, and methods. The most dominant chosen by students from the mapping results, and an analysis of the suitability between research topics, types of research, and research methods from several studies with similarities is carried out. From 2017 to 2019, two research topics always appeared and were the most dominant in the thesis of Biology Tadris students, namely research topics with the scope of Effect and Application, while the type of research that dominated the undergraduate dissertation of Biology IAIN Kerinci students, namely the qualitative kind of research. and the types of research and research methods most chosen by students are descriptive and experimental research methods